1996
DOI: 10.1007/bf00212432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liming on uptake of lead and cadmium by Raphanus sativa

Abstract: Although liming soil to reduce the heavy metal uptake by plants has been recommended generally, there is some disagreement with the practice based on the results of recent studies. Radishes, Raphanus sativa L. var. Paekyong, were grown in greenhouse pots which were filled with soils treated with 1.52 mg kg(-1) Cd and 25.37 mg kg(-1) Pb, respectively and amended with lime at five rates of 0, 0.25, 0.5, 1.0, and 2.0% by dry soil weight. Plants were harvested three times at 25, 50, and 75 days after sowing and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…There have been a number of studies showing the effect of soil pH changes on plant uptake of Cd. Han & Lee (1996) showed Cd uptake in radishes was significantly decreased after liming. Guttormsen et al (1995), examined the effect of soil pH on Cd uptake by cabbage and carrot during 3 years in a field trial, and at pH 5.5, Cd concentrations in cabbage and carrot were 23 and 46% higher than at pH 6.5.…”
Section: Plant CD Concentrationsmentioning
confidence: 92%
See 2 more Smart Citations
“…There have been a number of studies showing the effect of soil pH changes on plant uptake of Cd. Han & Lee (1996) showed Cd uptake in radishes was significantly decreased after liming. Guttormsen et al (1995), examined the effect of soil pH on Cd uptake by cabbage and carrot during 3 years in a field trial, and at pH 5.5, Cd concentrations in cabbage and carrot were 23 and 46% higher than at pH 6.5.…”
Section: Plant CD Concentrationsmentioning
confidence: 92%
“…However, soil pH is often regarded as the major variable controlling Cd uptake from soils (Chaney & Hornick 1978). A number of studies have shown that with increasing soil pH, there is a corresponding decrease in plant Cd concentrations (e.g., Han & Lee 1996). In contrast, however there have been several field trials in which liming to increase soil pH has resulted in no change in plant Cd concentrations (e.g., Sparrow et al 1993) and in some instances liming soil has increased plant Cd concentrations (e.g., Maier et al 1997;Singh & Myhr 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyapatite Increased immobilization through cation exchange, adsorption, surface complexation, precipitation and co-precipitation (Jeanjean et al, 1995;Mandjiny et al, 1998;Xu et al, 1994;Boisson et al, 1999;Seaman et al, 2001) Rock phosphate Increased immobilization through adsorption and precipitation Chen et al, 1997) K 2 HPO 4 Increased immobilization through phosphate-induced adsorption and precipitation (Pierzynski and Schwab, 1993;Pearson et al, 2000) KH 2 PO 4 Increased immobilization through phosphate-induced adsorption (Bolan et al, 1999b;Naidu et al, 1994) Ca(H 2 PO 4 ) 2 Increased immobilization through phosphate-induced adsorption (Bolan et al 1999b) (NH 4 ) 2 HPO 4 Increased adsorption due to an increase in pH, precipitation of Cd 3 (PO 4 ) 2 (Pierzynski and Schwab, 1993;Levi-Minzi and Petruzzelli, 1984;McGowen et al, 2001) CaCO 3 Increased immobilization through adsorption and precipitation; decreased plant uptake (Andersson and Siman, 1991;Bingham et al, 1979;Brown et al, 1997;Han and Lee, 1996;Chaney et al, 1977;He and Singh, 1994;Hooda and Alloway, 1996;John and Van Laerhoven, 1976;John et al, 1972;Lehoczky et al, 2000;Maclean, 1976;Oliver et al, 1996;Singh and Myhr, 1998;Singh et al, 1995;Tyler and Olsson, 2001) Ca(OH) 2 Decreased bioavailability (Basta and Sloan, 1999;Chaney et al, 1977;Brallier et al, 1996;Gray et al, 1999a) CaO Decreased phytoavailability (Vasseur et al, 1998) MgCO 3 Decreas...…”
Section: Referencementioning
confidence: 96%
“…Oliver et al [26] found that the effect of soil pH on the Cd concentration in wheat and barley grain was very small. Excessive liming may lead to a depression in crop yield [13]. In [2,10,11,28].…”
Section: Introductionmentioning
confidence: 99%